Practicum During the Covid-19 outbreak: Mapping the Decision-Making of University Education Departments - Σιάτρας, Αναστάσιος; Μιχαλοπούλου, Αικατερίνη (Education Sciences, 2020)
During the outbreak of the coronavirus SARS-CoV-2 in the spring semester 2019-2020, Education Departments of Greek Universities suspended practicum courses that were planned to be implemented into numerus education placements. In order to deal with problems related to practicum courses suspension, a number of Education Departments designed and implemented e-practicum distance learning programs. This paper focuses on mapping education strategies that were taken under consideration into Education Departments decision-making related to e-practicum distance learning programs. Content analysis was carried out either on formal decisions or published announcements of ten (10) Education Departments related to practicum courses. Analysis results highlight five (5) axes that allow the interpretation of the research findings. In conclusion, it is argued that education strategies related to e-practicum distance learning programs converge or diverge depending on education level to which University Education Departments correspond.